Pentingnya Pendidikan Islam Dalam Membentuk Karakter Anak Usia Dini - Insani Rizki Maulana; Jasiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Islamic education plays a crucial role in shaping the character of early childhood, as children are at a crucial stage of development that will determine their future personality. This article aims to explain the importance of Islamic education in instilling moral, spiritual, and social values ​​in children from an early age. The method used in writing this article is a literature review, reviewing various literature related to Islamic education and children's character development. The results of the study indicate that Islamic education can shape children's character through the instillation of noble morals, the habit of worship, discipline, responsibility, honesty, and respect for parents and the surrounding environment. Furthermore, the roles of family, school, and community are crucial factors in the success of Islamic-based character education. With the consistent implementation of Islamic education from an early age, children are expected to grow into individuals with faith, good morals, and the ability to face the challenges of modern development without losing their moral and religious values